MERLOT course eportfolios [electronic resource] - California State University System; MERLOT (Multimedia Educational Resource for Learning and Online Teaching).; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Long Beach, CA MERLOT, 2017)
Quoted from the homepage: A Course ePortfolio, an extension of a Bookmark Collection, provides MERLOT Members with the opportunity to also define strategic elements of a course (e.g., prerequisites, approach and outcomes, assessment, etc.). The MERLOT Course ePortfolio allows you to build your entire course ? from prerequisites to online resources to assessment ? all within MERLOT, and then share your Course ePortfolio with colleagues and students, or download it into a Word document and create your course syllabus. Additional information on Course ePortfolios can be found here.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; College teaching -- Electronic portfolios -- Open educational resources. .; Education, Higher -- Electronic portfolios -- Open educational resources. .